AN ANALYSIS OF TYPICAL CONDUCT PRACTICED WITHIN THE INTERNET: CYBER AND DIGITAL CRIMES (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present work takes an approach on the internet, which is undoubtedly an extremely useful and important tool in the present day, however, not only offers benefits to its users, because it is a little known world, where real dangers and enemies are Constantly present, provoking atrocities that surpass the barriers of the virtual and are materialized in the real world. The dark side of the Internet, known as Deep Web, will be unveiled where various illicit acts are practiced anonymously and freely, causing irreparable damage, surpassing the virtual field and reaching the social sphere, thus giving rise to so-called "virtual crimes or cyber crimes ". To curb such practices and effectively punish such criminal conduct is not an easy task, since the means used by the police to achieve this goal are ineffective, especially in the case of cyber criminals who act anonymously and leave no trace. Keywords: Internet.; Crimes.; Deep Web; Virtual; Laws.